Vasotocin mRNA Expression is Sensitive to Testosterone and Oestradiol in the Bed Nucleus of the Stria Terminalis in Female Japanese Quail. (20th August 2013) - Aste, N.; Sakamoto, E.; Kagami, M.; Saito, N.
<x xml:space="preserve">Abstract</x> Vasotocin‐producing parvocellular neurones in the medial part of the bed nucleus of the stria terminalis (BSTM) of many species of birds and mammals show sexual dimorphism and great plasticity in response to hormonal and environmental stimuli. In the BSTM of Japanese quail, vasotocin‐immunoreactive neurones are visible and sensitive to testosterone exclusively in males. In males, gonadectomy decreases and testosterone restores vasotocin‐immunoreactive cells and fibres by acting on vasotocin mRNA transcription. The insensitivity of female vasotocin‐immunoreactive neurones to the activating effects of testosterone is the result of organisational effects of early exposure to oestradiol. Female quail also show vasotocin mRNA‐expressing neurones in the BSTM, although it is not known whether the insensitivity of the vasotocinergic neurones to testosterone originates at the level of vasotocin gene transcription in this sex. Therefore, initially, the present study analysed the effects of acute treatment with testosterone on vasotocin mRNA expression in the BSTM of gonadectomised male and female quail using in situ hybridisation. Gonadectomy decreased (and a single injection of testosterone increased) the number of vasotocin mRNA‐expressing neurones and intensity of the vasotocin mRNA hybridisation signal similarly in both sexes. Notably, testosterone increased vasotocin mRNA expression in ovariectomised females over that shown by intact quail. However, this treatment had no effect on vasotocin immunoreactivity. A second experiment analysed the effects of testosterone metabolites, oestradiol and 5α‐dihydrotestosterone, on vasotocin mRNA expression in female quail. Oestradiol (but not 5α‐dihydrotestosterone) fully mimicked the effects of testosterone on the number of vasotocin mRNA‐expressing neurones and the intensity of the vasotocin mRNA hybridisation signal. Taken together, these results show, for the first time, that gonadal steroids strongly activate vasotocin mRNA expression in the BSTM of female quail.